Visible‐Light‐Driven Aerobic Photooxidation of Aldehydes to Methyl Esters Catalyzed by Riboflavin Tetraacetate. Issue 6 (24th February 2017) - Mühldorf, Bernd; Wolf, Robert
Abstract: Riboflavin tetraacetate (RFT) catalyzes the aerobic esterification of para ‐substituted benzaldehydes to their corresponding methyl esters. The reaction proceeds under visible‐light irradiation in MeOH/MeCN in the presence of a Brønsted acid such as HCl. Electron transfer from the in situ formed dimethyl acetal to the photoexcited triplet flavin appears to be a key mechanistic step. The acid catalyzes the formation of the acetal and increases the reduction potential of RFT by protonation. The photocatalyst is regenerated by reaction with atmospheric oxygen, which serves as the terminal oxidant. Abstract : Into the blue : The vitamin B2 derivative riboflavin tetraacetate (RFT) catalyzes the visible‐light‐driven esterification of aldehydes to the corresponding methyl esters under acidic conditions in a methanol/acetonitrile mixture. Electron transfer from the in situ formed dimethyl acetal to the photoexcited protonated 3 (RFTH + )* molecule appears to be key for the formation of the desired ester. Atmospheric oxygen is the terminal oxidant.